Criminal Histories and Rates of Recidivism Among Two Subtypes of Psychopathic Individuals - Weaver, Shelby S. (Criminal justice and behavior, 2022)
Although it is well established that individuals with psychopathic traits are a high-risk group for criminal recidivism, there is considerable evidence that psychopathy is a heterogeneous personality disorder comprised of two subtypes who differ on levels of negative affect (NA). However, few studies have examined differences in criminal histories, and fewer still have investigated differences in recidivism among subtypes of psychopathy. The current study compared criminal histories and recidivism rates between psychopathy subtypes differing in NA (high-NA vs. low-NA) within a sample of adult males incarcerated in state prisons. The high-NA and low-NA psychopathy subtypes did not differ on histories of total, nonviolent, or violent crime, and did not differ on rates of total, nonviolent, or violent recidivism. This finding highlights equally high levels of criminal risk associated with both subtypes of psychopathic individuals. Intervention strategies should be prioritized for both subgroups to effectively reduce the criminal costs associated with psychopathy.